2006
DOI: 10.1111/j.1365-2125.2006.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three cytochrome P450 inhibitors, ketoconazole, fluconazole, and paroxetine, on the pharmacokinetics of lasofoxifene

Abstract: AimsTwo studies were conduced to assess the effects of ketoconazole, a CYP3A4/5 inhibitor; fluconazole, a CYP2C9 inhibitor; and paroxetine, a CYP2D6 inhibitor, on lasofoxifene pharmacokinetics. MethodsThe first parallel group study was conducted in 45 healthy postmenopausal women (15 per group) to compare the pharmacokinetics of a single dose of lasofoxifene (0.25 mg) administered alone and in combination with ketoconazole (400 mg daily × 20 days) or fluconazole (400 mg daily × 20 days). Lasofoxifene was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Because oxidation accounts for about half of total lasofoxifene clearance and this pathway is further divided among multiple P450 isozymes, inhibition of a single enzyme will not have a clinically significant impact on the pharmacokinetics of lasofoxifene. Phase 2 clinical studies showed only modest increase in both the AUC and C max of lasofoxifene with concomitant administration of either ketoconazole, a potent inhibitor of CYP3A4 (Ouellet et al, 2006), or paroxetine, a potent inhibitor of CYP2D6 (Ouellet et al, 2006). Considering the large safety margin for lasofoxifene, no dosage adjustment is needed when coadministered with either CYP3A or CYP2D6 inhibitors (Ouellet et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because oxidation accounts for about half of total lasofoxifene clearance and this pathway is further divided among multiple P450 isozymes, inhibition of a single enzyme will not have a clinically significant impact on the pharmacokinetics of lasofoxifene. Phase 2 clinical studies showed only modest increase in both the AUC and C max of lasofoxifene with concomitant administration of either ketoconazole, a potent inhibitor of CYP3A4 (Ouellet et al, 2006), or paroxetine, a potent inhibitor of CYP2D6 (Ouellet et al, 2006). Considering the large safety margin for lasofoxifene, no dosage adjustment is needed when coadministered with either CYP3A or CYP2D6 inhibitors (Ouellet et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2 clinical studies showed only modest increase in both the AUC and C max of lasofoxifene with concomitant administration of either ketoconazole, a potent inhibitor of CYP3A4 (Ouellet et al, 2006), or paroxetine, a potent inhibitor of CYP2D6 (Ouellet et al, 2006). Considering the large safety margin for lasofoxifene, no dosage adjustment is needed when coadministered with either CYP3A or CYP2D6 inhibitors (Ouellet et al, 2006). However, as a result of these data, there is the potential for drug-drug interactions with any coadministered drug that is also eliminated by the same metabolic pathways, particularly those involving phase I oxidation by microsomal P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of loading doses resulted in reaching steady-state concentrations within approximately seven to nine days. The pharmacokinetics of lasofoxifene are linear over a wide dose-range (0.01 to 100 mg)57 and are not significantly affected by age, ethnicity, weight, moderately impaired hepatic or renal function, or medications such as warfarin, ketoconazole, and digoxin 6063. In a study of lasofoxifene disposition in healthy male subjects, it was eliminated by phase I oxidative metabolism (largely mediated by CYP2D6 and CYP3A4) and phase II conjugation 64…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Fluconazole (60 mg kg 1 , i.p.) was used as a positive control for enzyme inhibition studies [25]. For the 3 d treatments, rats were pre-treated with CuE (50-200 µg kg 1 day 1 , i.p.)…”
Section: Effects Of Cue Treatments On the Pharmacokinetics Of Tolbutamentioning
confidence: 99%
“…To determine the mechanism of CuE inhibition of tolbutamide 4-hydroxylase, a range of tolbutamide (25,50,75, 100 µmol L 1 ) and CuE (5, 10, 25, 50 µmol L 1 ) concentrations were used for inhibition kinetics studies. Sulfaphenazole (5-50 µmol L 1 ), a selective rat CYP2C11 inhibitor, was used as a positive control [21,22].…”
Section: Analysis Of Inhibition Kineticsmentioning
confidence: 99%